How do system-wide net-zero scenarios compare to sector model pathways for the EU? A novel approach based on benchmark indicators and index decomposition analyses - Matia Riemer; Jakob Wachsmuth; Baptiste Boitier; Alessia Elia; Khaled Al-Dabbas; Şirin Alibaş; Alessandro Chiodi; Felix Neuner (Energy Strategy Reviews, 2023)
The use of scenarios and quantitative modelling to identify pathways for energy system transformations in line with the Paris targets is well established in the field of energy and climate policy. The resulting decarbonization pathways depend on both assumptions and the type of model used (e.g., integrated assessment models, energy system, macro-econometric or bottom-up sector models). The objective of this article is to analyze how energy demand sectors in system-wide net-zero scenarios for the EU compare to the results of sector-specific models. To this end, a novel approach referred to as “sectoral benchmarking” is developed and applied, combining the application of standard indicators such as energy intensity, electrification rate or carbon intensity with an index decomposition analysis. The combined approach allows visualizing how system-wide decarbonization pathways differ from the sector models' pathways by bringing the model output in a harmonized format for an efficient comparison. The analysis compares pathways from four different modelling tools: two European system models, one of which is an energy system model (EU TIMES) and the other a macro-econometric model (NEMESIS); as well as two sector-specific models, for transport (ALADIN) and for the industry and building sectors (FORECAST). We evaluate the system model's net-zero scenarios by comparing them to a corridor given by the sector models' current policy and net-zero emission scenarios. This corridor represents what the sector models deem as plausible from their bottom-up perspective within the boundaries of current policies and ambitions to reach net-zero.Our results show that the system model net-zero pathways differ substantially from the sectoral perspective in all sectors. In the industry and building sectors, both system models' decarbonization ambitions are within the sector corridor, but the employed mitigation levers differ. In the industry sectors, the sectoral model achieves substantial CO2 emission reductions with electrification, while the system models use more bioenergy (EU TIMES) or more energy efficiency (NEMESIS). In the building sector, both system models rely mostly on electrification, while the sector models relies on biomass and some district heat and electrification. In the transport sector, both system models' decarbonization ambition is substantially lower than the sector model's.The observed differences are caused by a variety of factors, which we evaluate in this article. One reason is the system models' lower ambition to decarbonize the end-use sectors due to their ability to compensate with negative emission technologies across sectors. In addition, employed mitigation levers differ due to the models' differing capabilities to consider technologies as well as differences in the allocation of bioenergy to sectors.Our findings can be used to determine how the different types of models can inform each other and to make the diverging decarbonization pathways more transparent to policy-makers and other relevant stakeholders.